Polyester mesh dressings reduce delayed wound healing rates after total hip arthroplasty compared with silver-impregnated occlusive dressings - Carl L. Herndon, MD; Josephine R. Coury, MD; Nana O. Sarpong, MD, MBA; Jeffrey A. Geller, MD; Roshan P. Shah, MD, JD; H. John Cooper, MD (Arthroplasty Today, 2020)
Background: New dressings purport to reduce surgical wound complications after total hip arthroplasty (THA). This study compared delayed wound healing rates and reoperations between 2 increasingly popular dressings: a silver-impregnated occlusive (standard) dressing and a 2-octyl cyanoacrylate adhesive with polyester mesh. Methods: This retrospective cohort study reviewed 431 consecutive THAs performed by 2 surgeons between January 2017 and May 2019. One hundred and eight were excluded for not using standard or mesh dressings. A final 323 cases were separated into 2 cohorts: mesh (n = 186) and standard dressings (n = 137). Standard dressings were removed at 1 week. Mesh persisted until nonadherent, approximately 3-4 weeks. The surgeon assessed delayed wound healing at the 2-week postoperative visit. Secondary outcomes include deep infection and return to the operating room for a wound-related diagnosis. Differences were determined using the chi-square test. Results: There were no demographic, comorbidity, or surgical differences between groups. There were 22 total cases of delayed wound healing with 7 (3.8%) in the mesh group and 15 (10.9%) in the standard dressing group (P = .01). There were no significant differences in reoperations (2 [1.1%] vs 2 [1.5%], P = .76) or deep infections (2 [1.1%] vs 1 [0.7%], P = .75). Conclusions: Mesh dressings are a safe and reliable dressing type for THA and were associated with a decrease in early wound healing complications when compared with standard, silver-impregnated occlusive dressings in this retrospective series. The mesh tension sharing properties and longer duration of occlusive protection may explain this difference. Level of Evidence: Level III.